Cladribine Ameliorates Imiquimod Induced Murine Psoriasiform Dermatitis - Xue J; Shu D; Zhao Y (Clinical, Cosmetic and Investigational Dermatology)
Jingwen Xue,1,2 Dan Shu,1,2 Yi Zhao1,2 1Department of Dermatology, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, Beijing, 102218, People’s Republic of China; 2Photomedicine Laboratory, Institute of Precision Medicine, Tsinghua University, Beijing, People’s Republic of ChinaCorrespondence: Yi Zhao, Department of Dermatology, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, No. 168 Litang Road, Changping District, Beijing, 102218, People’s Republic of China, Email zhaoyimd@tsinghua.edu.cnBackground: Significant progress has been made in understanding the mechanisms of psoriasis, particularly the role of the interleukin (IL)-23/T-helper (Th) 17 axis, leading to novel, targeted therapies. However, many patients develop resistance to treatment over time. Thus, exploring new therapeutic strategies for severe refractory psoriasis remains crucial.Objective: To investigate the effect of cladribine on imiquimod induced psoriasiform dermatitis in mice.Methods: We established an imiquimod (IMQ)-induced psoriasiform dermatitis mouse model to investigate cladribine’s effects on skin immune cells. Mice were allocated to five groups: Control, IMQ, High-dose cladribine (30mg/kg), Low-dose cladribine (20mg/kg), and Methotrexate. We assessed cumulative scores, skin pathology, immunohistochemistry, flow cytometry, and serum cytokines. We also studied cladribine’s long-term efficacy by reapplying IMQ for a second round (7 days) after five half-lives of cladribine.Results: Cladribine significantly ameliorated symptoms and pathological features of IMQ-induced psoriasis in both high and low-dose groups, with efficacy comparable to methotrexate. Cladribine dose-dependently reduced Th17 and Th1 cell frequencies in psoriatic skin, along with associated cytokines. High-dose cladribine demonstrated sustained inhibition of IMQ-induced psoriasis.Conclusion: These findings indicate that cladribine can ameliorate imiquimod-induced psoriasiform dermatitis in mice, exhibiting a dose-dependent and sustained therapeutic effect.Keywords: cladribine, imiquimod-induced murine model, psoriasis